Trapped at home: The effect of mothers' temporary labor market exits on their subsequent work career - Nina Drange; Mari Rege (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper investigates how mothers' decision to stay at home with young children affects their subsequent work careers. Identification is based on the introduction of the Cash-for-Care program in Norway in 1998, which increased mothers' incentives to withdraw from the labor market when their child was one and two years old. Our estimates demonstrate that the program had effects on earnings and full-time employment even when the child was no longer eligible for Cash-for-Care at ages four and five. However, from age six, we can no longer see any effects. The effects seem to dissipate because most mothers remained attached to the labor force through part-time employment.
Keywords: J13; J21; J24; 330; female labor supply; family; home production; parental leave; Familienleistungsausgleich; Kinderbetreuung; Wirkungsanalyse; Weibliche Arbeitskräfte; Arbeitsangebot; Norwegen